Vaccination in delivery wards leads to high timely coverage of hepatitis B birth dose vaccine in Islamabad-Pakistan, 2023 - Huma Qureshi,; Mahmood, Hassan; Alam, Syed; Aabroo, Atiya; Channa, Zafar Iqbal; Shaheen, Asma; Fatima, Zofishan Jabeen; Glass, Nancy; Khetsuriani, Nino; Kazi, Muhammad Ahmed Kazi; Tohme, Rania A. (Journal of the Pakistan Medical Association, 2025)
Despite a high burden of hepatitis B in Pakistan, administration of hepatitis B birth dose (HepB-BD) has not been introduced on a national level and timely coverage remains low in selected provinces where the vaccine is available. This project was undertaken to assess the ease of timely (within 24 hours of birth) administration of HepB-BD by delivery nurses. A total of 1,000 HepB-BD doses were provided to delivery units of two public tertiary care hospitals in Islamabad. Out of 2,008 births in three months, 2,000 (99.6%) were vaccinated with HepB-BD. Out of 1,986 new-borns with available time of vaccine administration, all received the vaccine within 24 hours of birth with 98.3% receiving the vaccine within an hour of delivery. Delivery wards are the best setting to provide HepB-BD. Provinces that are already procuring HepB-BD and future nationwide introduction of HepB-BD in Pakistan could use lessons from this pilot study to ensure high coverage with timely administration of HepB-BD. Keywords: Hepatitis B birth dose, Immunisation, Mother to child transmission, Expanded programme for immunisation.